Job stress and patient safety culture: a qualitative study among hospital nurses in Palestine - Loai M. Zabin; Jamal Qaddumi; Sajed Faisal Ghawadra; Maher M. Battat (BMC Nursing)
Abstract Background In recent years, the healthcare industry has witnessed growing concern over patient safety culture, with a specific focus on the role of nursing professionals. This research explores the intricate dynamics between job-related stress and patient safety culture perceptions among hospital nurses in Palestine. Methods This study employed a qualitative, interpretative phenomenological approach to explore the lived experiences of nurses. A purposive sampling strategy was used to select seven registered nurses from multiple hospital units across the North West Bank, Palestine. The participants were selected based on criteria including a minimum of one year of clinical experience, experience in diverse hospital units, and willingness to share their experiences. Special emphasis was placed on including nurses with a Master’s degree in nursing because of their potential for advanced insights and the high percentage of nurses with this degree in Palestine. In-depth semi-structured interviews, lasting approximately 28–40 min each, were conducted in September 2023. Three interviews were conducted via Zoom, and four were conducted face-to-face. Thematic analysis was used to identify key themes and patterns. The small sample size was justified by the study’s focus on in-depth exploration of individual experiences and the achievement of thematic saturation. Results The study findings revealed six main themes: five related to patient safety culture and three related to job stress. Factors such as teamwork, workload, staffing, communication, conflict with colleagues, lack of support, and error reporting significantly influence job stress and patient safety culture. The study suggested that job stress has a negative effect on the perception of patient safety culture. Notably, support for nurses in managing job stress was primarily at the individual level, with limited hospital-based initiatives. Conclusion This study emphasized the importance of customized policies and interventions to address nurses’ specific stressors and improve hospital patient safety culture. Additionally, it highlighted the distinct challenges encountered by Palestinian nurses, including resource limitations and staffing issues. These factors intensify job stress and could increase job stress and impact patient safety. Recognizing these contextual nuances is essential for designing focused interventions and support systems that prioritize nurses’ overall well-being and enhance the quality of patient care. Hospital administrations should also focus on implementing coping mechanisms to help nurses manage stress and mitigate its effects on their well-being and patient outcomes.